Mapping Intercultural Dialogue Networks In Multicultural Schools: A Social Network Analysis Of Teachers, Students, And Community Actors - Agustina Tri Wijayanti; Taryatman Taryatman; Zaenal Abidin; Husni Thamrin; Rizal Bakti (Yayasan Darussalam Bengkulu, 2026)
Intercultural dialogue in multicultural schools is sustained by relational ties among teachers, students, school leaders, and community actors, yet its structural configuration remains insufficiently mapped in Indonesian school contexts. This study addresses this gap by applying a hybrid Systematic Literature Review and Social Network Analysis (SLR-SNA) approach to identify central actors, brokers, communities, and structural vulnerabilities in intercultural dialogue networks. Literature was retrieved from Scopus and Google Scholar using database-specific search strings on intercultural dialogue, multicultural schooling, school actors, and network relations. Following PRISMA-compliant screening of publications from 2020 to 2025, 32 articles were retained. Actor-programme relationships were extracted through a predefined codebook and transformed into a two-mode matrix comprising 55 nodes and 161 undirected, unweighted edges. The network was analysed in Gephi 0.10.1 using degree, betweenness, closeness, bridging coefficient, and Louvain modularity. Results: Four communities emerged: Teacher Actors (C0), Student Actors (C1), Community Actors (C2), and School Leadership (C3). School Leadership occupied the most dominant brokerage position, with the School Principal recording the highest degree (17) and betweenness centrality (102.40). Student actors showed the strongest intercommunity connectivity, whereas community actors had high bridging coefficients but low integration, indicating unrealised bridging potential. The network density was 0.109 and modularity reached Q = 0.524, indicating a sparse and fragmented dialogue ecosystem. These findings reveal a leadership-dominated, student-intermediated, and community-marginalised network architecture. Strengthening intercultural dialogue therefore requires institutionalising community participation, distributing student bridging roles, and reducing excessive dependence on school leadership.